Dengue Fever and International Travel. Issue 6 (19th July 2013) - Ratnam, Irani; Leder, Karin; Black, Jim; Torresi, Joseph
Abstract : Background: Dengue is a leading public health problem with an expanding global burden. Dengue virus is also a significant cause of illness in international travelers with an increasing number of cases of dengue fever identified in travelers returning from dengue‐endemic countries. Methods: This review focuses on the clinical illness of dengue infection in international travelers and provides a summary of the risk of infection for travelers, clinical features of infection, and an overview of dengue vaccines and their potential applicability to travelers. Results: Four prospective studies of travelers to dengue‐endemic destinations have shown that the dengue infection incidence ranges from 10.2 to 30 per 1, 000 person‐months. This varies according to travel destination and duration and season of travel. Dengue is also a common cause of fever in returned travelers, accounting for up to 16% of all febrile illnesses in returned travelers. Although the majority of infections are asymptomatic, a small proportion of travelers develop dengue hemorrhagic fever. The diagnosis of dengue in travelers requires a combination of serological testing for IgG and IgM together with either nucleic acid or NS1 antigen testing. Several vaccine candidates have now entered into clinical trials including ChimeriVax Dengue, which is currently in phase 3 trials, live‐attenuated chimeric vaccines (DENV‐DENV Chimera, Inviragen), live‐attenuated viral vaccines, recombinant protein subunit vaccines, and DNA vaccines. Conclusions: Dengue infection in international travelers is not infrequent and may be associated with substantial morbidity. Furthermore, an accurate diagnosis of dengue in travelers requires the use of a combination of diagnostic tests. Although a vaccine is not yet available a number of promising candidates are under clinical evaluation. For now travelers should be provided with accurate advice regarding preventive measures when visiting dengue‐endemic areas.